Professoras iniciantes e bem-sucedidas: análise das estratégias didáticas de professoras bem-sucedidas no início de carreira - Gomes, Fernanda Oliveira Costa (2020)
This research has as its theme the work of teachers considered successful at the beginning of their careers and their strategies for overcoming the difficulties inherent to teaching. The curiosity about the subject presented arose from the anguishes, idealizations, frustrations and achievements of my own experience in the teaching career, both at work as a primary school teacher and as a higher education professor. For this reason, the didactic difficulties of elementary school teachers were the object of study in a research developed by me in 2013 and defended in 2014 at master's degree. Once the objectives of the research were achieved, other doubts arose and other curiosities were expressed. Because of this, the present research is based on the following problem: Faced with the difficulties inherent in the teaching profession, what are the didactic procedures or strategies that teachers considered successful developed to achieve the objectives of their profession? In order to answer this question, the interview and observation procedures were used for data collection. Three female novice elementary school teachers, working in public schools in the city of São Paulo, participated in the survey. They are: Júlia, Alice and Sofhia (fictitious names). The observations occurred from June 2017 to May 2018. The interviews took place gradually from the teachers' HA (Activity Hour) schedules. The theoretical framework used in the research is composed of three theoreticians: Pierre Bourdieu, Michael Huberman and Alda Junqueira Marin. From Bourdieu's studies the concept of Habitus will be used. Huberman's studies subsidize a categorization of the teachers' life cycle, especially the concepts referring to the beginning of a career ― "reality shock" and "exploration" ― are indispensable. In relation to Didactics, Marin's studies will be used, which defines the features of Didactics